Heat‐Tolerant QTLs Associated with Grain Yield and Its Components in Spring Bread Wheat under Heat‐Stressed Environments of Sudan and Egypt. Issue 1 (1st January 2019) - Tadesse, W.; Suleiman, S.; Tahir, I.; Sanchez-Garcia, M.; Jighly, A.; Hagras, A.; Thabet, Sh.; Baum, M.
Abstract : Heat stress decreases photosynthesis, pollen viability, and grain number and weight and hence lowers yield and quality of wheat ( Triticum aestivum L.) by variable amounts among different cultivars and genotypes. The present study was performed to determine genetic variability of spring bread wheat genotypes for yield and other agronomic traits under heat‐stressed (Wad Medani, Sudan) and high‐yielding (Sids, Egypt) environments and to identify linked single nucleotide polymorphism (SNP) markers through association mapping. A heat association panel of 197 spring wheat genotypes from ICARDA was evaluated for yield and agronomic traits at Wad Medani and Sids stations for 2 yr (2014–2015). A total of 111 significant marker‐trait associations were detected. The wsnp_Ex_c12812_20324622 marker on chromosome 4A was significantly correlated with yield at both locations. At Wad Medani, wsnp_Ex_c2526_4715978 on chromosome 5A was significantly correlated with grain yield. Wheat genotypes carrying the cytosine base at the wsnp_Ex_c12812_20324622 and wsnp_Ex_c2526_4715978 markers outyielded the ones carrying the alternative bases by 15%, whereas genotypes carrying the cytosine base at only one of the two markers increased their yield by 7.9 to 10%, suggesting the importance of using these markers for marker‐assisted selection in breeding programs to increase yield under heat stress. The top 20 high‐yielding and heat‐tolerant genotypes identified in this study have been distributed to the national research systems of Central and West Asia and North Africa (CWANA) and sub‐Saharan Africa (SSA) for potential direct release and/or use as parents after local adaptation trials.